Epidemiology of prehospital trauma deaths in Malawi: A retrospective cohort study - Mulima, Gift (Afr J Emerg Med, 2021)
INTRODUCTION: Trauma is among the leading causes of death and disability in both adults and children worldwide. In Malawi, trauma patients are commonly brought in dead (BID). We aimed to describe the prevalence, sociodemographic, and injury-related characteristics of patients BID to Kamuzu Central Hospital (KCH), a referral hospital in Lilongwe, Malawi. METHODS: We retrospectively reviewed records of all patients BID in the trauma surveillance registry at KCH from February 2008 to September 2019. We excluded patients BID that did not present to the emergency centre, and were instead taken to the mortuary directly. We used descriptive statistics to evaluate the epidemiology of patients BID. RESULTS: We reviewed 106,198 trauma records and 1889 (1.8%) were BID patients. Most patients BID were male, in both adult (n = 1337/1528, 88.4%) and children (n = 231/360, 64.9%) cohorts. The mean age was 34.7 (SD 11.9) years in adults and 7.8 (SD 5.4) years in children. Among the adult BID patients, 33.2% were unemployed, 25.6% were construction workers, and 10.1% were small business owners or managers. The common injury mechanisms in adults were road traffic-related injuries (RTIs) (47.1%) and assaults (23.6%). In children, injuries resulted from RTIs (39.7%), with 74.4% of those were pedestrians hit by cars, drowning (22.9%), and burns (12.4%). In both groups, most injuries occurred on roads (60.2%) or at home (22.1%). Reported alcohol use at the time of trauma was present in 6.3%. The police (57.9%) and privately-owned vehicles (26.6%) transported most BID patients to KCH. CONCLUSION: Efforts to reduce prehospital trauma mortality must focus on improving prehospital care, including training the police and community in basic life support and improving resources towards prehospital trauma care. Further efforts to reduce prehospital mortality must aim to decrease injuries on the roads and at home.